2017
DOI: 10.1021/acs.energyfuels.7b01843
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Guerbet Alcohol Ethoxylates for Surfactant–Polymer Flooding Free of Alkali

Abstract: Two series of double-chain single-head nonionic surfactants, Guerbet alcohol ethoxylates (C m GA–E n ; m = 16 and 20, n = 5.7–24.0), were synthesized, and their performances as surfactants for surfactant–polymer (SP) flooding free of alkali were evaluated. The products have relatively low critical micelle concentrations [(6.8 × 10–7)–(1.0 × 10–5 mol/L)] and a wide range of surface tensions at the critical micelle concentration (γcmc) values (30.3–38.0 mN/m) at 25 °C, depending on both the alkyl-chain length an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…The operation was repeated until ultralow IFT can no longer be achieved. The total adsorption time is taken as a measure of the resistance against adsorption by the sandstone (Yan et al, , , ). The connate water has a pH of 9.1 in which the sandstones are negatively charged and no extra alkali or acid was added into the dispersion (Cui et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…The operation was repeated until ultralow IFT can no longer be achieved. The total adsorption time is taken as a measure of the resistance against adsorption by the sandstone (Yan et al, , , ). The connate water has a pH of 9.1 in which the sandstones are negatively charged and no extra alkali or acid was added into the dispersion (Cui et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…Yan et al 2 reported that a nonionic/zwitterionic formulation with polyacrylamide achieved four times the ultralow IFT (ESI Table 11 †). Fig.…”
Section: 91020mentioning
confidence: 99%
“…[1][2][3][4] However, the alkali in the ASP system simultaneously resulted in the reduction of reservoir permeability due to the dispersion and migration of clay and the alkaline scaling in formation. 5 Alkalifree binary surfactant-polymer (SP) ooding with ultralow interfacial tension (#10 À3 mN m À1 ) is a promising approach among tertiary oil recovery methods.…”
mentioning
confidence: 99%
See 2 more Smart Citations